2010
DOI: 10.1038/leu.2010.231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjunct cytogenetic abnormalities for prognostic stratification in patients with myelodysplastic syndrome and deletion 5q

Abstract: This cooperative study assessed prognostic factors for overall survival (OS) and risk of transformation to acute myeloid leukemia (AML) in 541 patients with de novo myelodysplastic syndrome (MDS) and deletion 5q. Additional chromosomal abnormalities were strongly related to different patients' characteristics. In multivariate analysis, the most important predictors of both OS and AML transformation risk were number of chromosomal abnormalities (Po0.001 for both outcomes), platelet count (Po0.001 and P ¼ 0.001,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
86
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 26 publications
(35 reference statements)
7
86
0
1
Order By: Relevance
“…5,6 (4) The presence of more than one additional chromosomal aberration is associated with an increased risk of progression. This is in line with the only large study evaluating progression features in patients affected with del(5q) that was recently presented by Mallo et al 16 This study focused primarily on cytogenetic features, comprising 541 patients with different French-American-British subtypes of MDS, including patients with medullary blasts of up to 20% with or without additional chromosomal abnormalities. Chromosomal complexity, platelet count and percentage of marrow blast were the most important factors predictive for the risk of AML progression in that study.…”
Section: Discussionsupporting
confidence: 70%
“…5,6 (4) The presence of more than one additional chromosomal aberration is associated with an increased risk of progression. This is in line with the only large study evaluating progression features in patients affected with del(5q) that was recently presented by Mallo et al 16 This study focused primarily on cytogenetic features, comprising 541 patients with different French-American-British subtypes of MDS, including patients with medullary blasts of up to 20% with or without additional chromosomal abnormalities. Chromosomal complexity, platelet count and percentage of marrow blast were the most important factors predictive for the risk of AML progression in that study.…”
Section: Discussionsupporting
confidence: 70%
“…A recent cooperative study revealed that patients with one defect in addition to del(5q) presented an OS similar and a risk of AML transformation higher than those of patients with del(5q) alone [44]. Intriguingly, a current SNP-A report showed that deletions involving the centromeric or telomeric extremes of 5q are associated with a more aggressive disease phenotype and additional chromosomal lesions [45].…”
Section: Discussionmentioning
confidence: 98%
“…The "5q-syndrome" was first described by Van den Berghe in 1974 with distinct morphologic features which include thrombocytosis, macrocytic anemia, and hypolobulated megakaryocytes, along with minimal dysplasia in the granulomonocytic and erythroid lineages [35]. Among patients with MDS with del(5q), the presence of an additional nonhigh-risk cytogenetic abnormality has not been shown to have an adverse impact on the otherwise favorable prognosis [36]. On the other hand, studies have confirmed that the presence of TP53 mutations confers adverse prognosis to del(5q) patients [37,38].…”
Section: Introductionmentioning
confidence: 99%